Advances in parasitology. Vol. 52 - Baker, John R. (John Robin); Muller, Ralph; Rollinson, D.; ScienceDirect eBooks (Amsterdam ; London : Academic, 2002)
First published in 1963, Advances in Parasitology contains comprehensive and up-to-date reviews in all areas of interest in contemporary parasitology. Now edited by J.R. Baker (Royal School of Tropical Medicine and Hygiene, UK), R. Muller (International Institute of Parasitology, UK) and D. Rollinson (The Natural History Museum, UK), supported by an international Editorial Board, Advances in Parasitology includes medical studies on parasites of major influence, such as typanosomiasis and scabies, and reviews of more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications. Eclectic volumes are supplemented by thematic volumes on such topics as Remote Sensing and Geographical Information Systems in Epidemiology. Key Features: * First in the ISI Parasitology List in 2000 * ISI Impact Factor of 6.724 in 2000 * Series encompasses over 35 years of parasitology coverage.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Parasitology; Parasitology; Electronic books